A Note on Historical Mortality in a Northern Bison Population - Ferguson, Theresa A.; Laviolette, Frank (ARCTIC, 1992)
Mortality of bison in the area of what is now Wood Buffalo National Park was recorded in records of Fort Chipewyan for the years 1821, 1823, and 1831. There is oral tradition in the Fort Smith area that many bison died in the Slave River lowlands during one summer later in the 19th century. The records of sudden death among bison during the summer resemble features of anthrax mortality that occurred among bison in the same general area between 1962 and 1978. This suggests that anthrax may have a much longer history in the region than recognized previously.Key words: northern bison, disease, ethnohistory, anthrax RÉSUMÉ. La mortalité du bison dans la région qui est maintenant devenue le parc national Wood Buffalo est inscrite sur les registres de Fort Chipewyan pour les années 1821, 1823 et 1831. Il existe une tradition orale dans la région de Fort Smith disant que de nombreux bison périrent dansles basses terres de la rivière Slave au cours d’un été de la fin du XIXe siècle. Les registres des morts soudaines parmi les bisons durant la saison d’été rappellent les caractéristiques de la mortalité due à l'antrax qui a touché les bisons à peu près dans la même zone entre 1962 et 1978. Cela laisseà penser que l’anthrax peut avoir dans cette région une histoire beaucoup plus ancienne qu’on ne l’admettait précédemment.Mots clés: bison des bois, maladie, ethnohistoire, anthrax